2016
DOI: 10.2147/jpr.s113138
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary evaluation of the relationship of cannabinoid blood concentrations with the analgesic response to vaporized cannabis

Abstract: A randomized, placebo-controlled crossover trial utilizing vaporized cannabis containing placebo and 6.7% and 2.9% delta-9-tetrahydrocannabinol (THC) was performed in 42 subjects with central neuropathic pain related to spinal cord injury and disease. Subjects received two administrations of the study medication in a 4-hour interval. Blood samples for pharmacokinetic evaluation were collected, and pain assessment tests were performed immediately after the second administration and 3 hours later. Pharmacokineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 51 publications
1
38
1
Order By: Relevance
“…The high variability in the PK of CBD and its metabolites in this trial is common with other cannabinoids . During validation of the bioanalytical method to quantify CBD and metabolite plasma concentrations, recovery of CBD was low at 45.4%‐48.8%; however, recovery levels were consistent across the assay range and sufficient to achieve adequate method sensitivity.…”
Section: Discussionmentioning
confidence: 94%
“…The high variability in the PK of CBD and its metabolites in this trial is common with other cannabinoids . During validation of the bioanalytical method to quantify CBD and metabolite plasma concentrations, recovery of CBD was low at 45.4%‐48.8%; however, recovery levels were consistent across the assay range and sufficient to achieve adequate method sensitivity.…”
Section: Discussionmentioning
confidence: 94%
“…The large total subject variability in this trial is common with cannabinoids, and similar levels of variability have been previously reported in other trials with cannabinoids. 23,24 Although the PK of CBD and its metabolites have been explored following a single administration in this trial, exposures have been reported following multiple bidaily administration; results show there is no significant time dependency in the PK other than accumulation approximating to 3-fold for the parent drug CBD. 25 It is anticipated this single-dose assessment would predict the extent of change in drug clearances observed following multiple administration.…”
Section: Discussionmentioning
confidence: 94%
“…Growing evidence suggests that MM is useful in the treatment of neuropathic pain . The majority of these studies used inhaled marijuana.…”
Section: Clinical Usementioning
confidence: 99%
“…15 There is little good-quality evidence studying the role of MM in depression specifically, although some trials investigating synthetic cannabinoids in pain assessed mood as a secondary outcome, and these did not suggest an effect on depression. 33,34 Nociceptive pain 22 Weak Neuropathic pain [17][18][19][20][21] Moderate Spasticity 23 Moderate Nausea and vomiting 9,15,29 Moderate Anorexia 9,30 Moderate Neurological and psychiatric illness 9,15,[31][32][33][34] Mixed (see text)…”
Section: Neurological and Psychiatric Illnessmentioning
confidence: 99%